2004ネン ナンキョク ニオケル イリョウ イガク ケンキュウ ニカンスル ケンキュウ シュウカイ ノ ホウコク - 大野, 義一朗; オオノ, ギイチロウ; 福地, 光男; フクチ, ミツオ; 大野, 秀樹; オオノ, ヒデキ; 森本, 武利; モリモト, タケトシ; 三上, 春夫; ミカミ, ハルオ; 宮田, 敬博; ミヤタ, タケヒロ; et al. (2005)
P(論文) 004年の「南極における医療・医学研究集会」が8月28日,国立極地研究所で開催された.主な内容は「南極の高所がヒトに与える影響」,「南極でのストレスがアミノ酸脂肪酸代謝に与える影響」,「越冬基地におけるレジオネラ菌調査」,「南極における紫外線障害とその対策」,「46次隊の医学研究計画」であった.16施設から合計22名が参加し,口頭発表10演題,ポスター発表1演題,文書発表1演題について,活発な討論が行われた. A meeting on Antarctic Medical Research was held at NIPR on August 28, 2004. Twenty two members participated in the meeting with ten oral presentations, one poster presentation and one report paper. The main subjects were The human responses in the Antarctic highland", The influence of the cold stress on the amino acids and lipid metabolism", Legionella contamination at the Antarctic wintering stations". The JARE-46 medical research program" was also reported and discussed. departmental bulletin paper